2005
DOI: 10.1007/s00125-005-1835-y
|View full text |Cite
|
Sign up to set email alerts
|

Changes in adiponectin receptor expression in muscle and adipose tissue of type 2 diabetic patients during rosiglitazone therapy

Abstract: Aims/hypothesis: Adiponectin is important in the regulation of insulin sensitivity in man. Its receptors, adipoR1 and R2, have recently been identified, but their expression in adipose tissue and their regulation in response to insulin sensitisation of diabetic patients have never been assessed. We therefore explored the regulation of adipoR1/R2 and adiponectin expression in adipose tissue and skeletal muscle, and of adiponectin plasma concentrations in response to insulin sensitisation by rosiglitazone. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(41 citation statements)
references
References 12 publications
3
35
1
2
Order By: Relevance
“…The second important observation from our present study is that rosiglitazone administration to type 2 diabetes patients for 12 weeks induced PCK1 mRNA, but not PCK2 mRNA, in s.c. adipose tissue at a much higher incremental level than that of any other gene tested in the same cohort [8,40,41]. Similar results were obtained by Bogacka et al in a cohort of pioglitazone-treated type 2 diabetes patients [22].…”
Section: Discussionsupporting
confidence: 82%
“…The second important observation from our present study is that rosiglitazone administration to type 2 diabetes patients for 12 weeks induced PCK1 mRNA, but not PCK2 mRNA, in s.c. adipose tissue at a much higher incremental level than that of any other gene tested in the same cohort [8,40,41]. Similar results were obtained by Bogacka et al in a cohort of pioglitazone-treated type 2 diabetes patients [22].…”
Section: Discussionsupporting
confidence: 82%
“…Thus, Tan et al 36 could not find any correlation between APM1 expression and receptor expression in subcutaneous abdominal fat of patients with DM2. Rasmussen et al 29 on the other hand, reported higher expression of AdipoR1 than AdipoR2 in both SAT and VAT in a group of obese non-diabetic women.…”
Section: Discussionmentioning
confidence: 89%
“…specifically, adiponectin could control insulin sensitivity mainly by modulating non-oxidative glucose disposal, i.e. the glycogen synthesis pathway in human skeletal muscle (50). It is interesting to note that plasma adiponectin levels correlated significantly with FFA levels at baseline, and during rosiglitazone treatment, the changes of adiponectin and clamp FFA concentrations were significantly and negatively associated.…”
Section: Discussionmentioning
confidence: 94%